Non-explosive training Grenade for the Schools of the Colombian Military Forces and Police - Garay Rairán, Fabián; Parra Laguna, Diego Mauricio; Tarazona, Nathalie; Conde, Julián (Ingeniería Solidaria, 2021)
Introduction: The paper is a product of the research “Non-explosive training grenade Design for the practice and launch exercise in the training schools of Colombian military forces” carried out in the Escuela Militar de Suboficiales during 2017 and 2020. Problem: Material mishandling during training sessions can lead directly to the injury of training personnel. Objective: The research aims to design a Non-explosive training grenade to avoid accidents during launching exercises in the training schools of the Colombian military forces and Police. Methodology:The transmission and reception elements, display, and sounds items were implemented through electronic devices, seeking to obtain a device that mimics the original grenade during training exercises; the IM 26. Results:12 prototypes of low-cost non-explosive training grenades were built for the market in ABS material with triggers and ejectors in steel, which emulate, in dimension and weight, a real IM26 grenade. Conclusion:The prototype meets the minimum usage, size, and mass requirements that emulate the original, the time after being primed, and the execution sound after being released. Originality:These unique prototypes in Colombia allow mitigating possible incidents in the training school’s grenade-throwing exercises. Limitations:The transmission and reception modules (433 MHz) did not have enough power to transmit the data over a range greater than 50 m; the radiofrequency system SYNAPSE was used.
Keywords: grenade; emulation; non-explosive; radiofrequency; training